Macroprudential Policy, Incomplete Information and Inequality : The case of Low-Income and Developing Countries - Rubio, Margarita (IMF Working Papers; Working Paper ;, 2017)
In this paper, we use a DSGE model to study the passive and time-varying implementation of macroprudential policy when policymakers have noisy and lagged data, as commonly observed in lowincome and developing countries (LIDCs). The model features an economy with two agents; households and entrepreneurs. Entrepreneurs are the borrowers in this economy and need capital as collateral to obtain loans. The macroprudential regulator uses the collateral requirement as the policy instrument. In this set-up, we compare policy performances of permanently increasing the collateral requirement (passive policy) versus a time-varying (active) policy which responds to credit developments. Results show that with perfect and timely information, an active approach is welfare superior, since it is more effective in providing financial stability with no long-run output cost. If the policymaker is not able to observe the economic conditions perfectly or observe with a lag, a cautious (less aggressive) policy or even a passive approach may be preferred. However, the latter comes at the expense of increasing inequality and a long-run output cost. The results therefore point to the need for a more careful consideration toward the passive policy, which is usually advocated for LIDCs.